2017
DOI: 10.1101/170902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterosis is a systemic property emerging from nonlinear genotype-phenotype relationships: evidence fromin vitrogenetics and computer simulations

Abstract: Heterosis, the superiority of hybrids over their parents for quantitative traits, represents a crucial issue in plant and animal breeding. Heterosis has given rise to countless genetic, genomic and molecular studies, but has rarely been investigated from the point of view of systems biology. We hypothesized that heterosis is an emergent property of living systems resulting from frequent concave relationships between genotypic variables and phenotypes, or between different phenotypic levels. We chose the enzyme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 157 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…Heterosis is the expression of dominance deviation, a variance from mid parent value, which may be explained by the additive effects of several desired dominant alleles, or as 'overdominance' the combined effect of two different alleles at the same gene locus, or a combination of both [109][110][111][112] . From the de nition, heterosis helps a breeder to make more stringent selections.…”
Section: Discussionmentioning
confidence: 99%
“…Heterosis is the expression of dominance deviation, a variance from mid parent value, which may be explained by the additive effects of several desired dominant alleles, or as 'overdominance' the combined effect of two different alleles at the same gene locus, or a combination of both [109][110][111][112] . From the de nition, heterosis helps a breeder to make more stringent selections.…”
Section: Discussionmentioning
confidence: 99%
“…Heterosis, defined as the superiority of hybrids over their parents for quantitative traits, represents by crossbreed organisms as compared with inbred, as the results of dissimilar in the constitution of the uniting parental gametes [70,22]. Heterosis exploitation is the most important in agriculture, which was added improved genotype in the production of crops and animals during the last of 20 th century [18,62].…”
Section: Heterosis and Inbreeding Depressionmentioning
confidence: 99%
“…It might be due to different factors of genetic effects; namely: dominance, overdominance and epistasis effects. While substantial debated on dominance or over-dominance effects, evidence of different studies indicated that both are not mutually exclusive [22].…”
Section: Standard Heterosis (Sh%) =mentioning
confidence: 99%
“…The respective parts of the various genetics effects in heterosis depends on the trait, the species and the genetic material (Xiao et al 1995;Huang et al 2016;Seymour et al 2016). Altogether, heterosis appears to be a pervasive phenomenon, accounted for by the common non-linearity of the genotype-phenotype map (Wright 1934;Omholt et al 2000;Fiévet et al 2018).…”
mentioning
confidence: 99%